2022
DOI: 10.1021/acssuschemeng.1c08285
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Electrochemical Synthesis of Hydrogen Peroxide (H2O2) Enabled by Amino Acid Glycine-Derived Metal-Free Nitrogen-Doped Ordered Mesoporous Carbon

Abstract: Electrocatalytic partial oxygen reduction has been considered a more sustainable approach to the synthesis of hydrogen peroxide (H2O2), as compared with current industrial anthraquinone processes. One key research need is to explore low-cost active electrocatalysts. Here, we report a facile, solvent-free method to synthesize a metal-free nitrogen-doped ordered mesoporous carbon (N-OMC) by in situ transforming of glycine (carbon and nitrogen precursors) in the mesoporous SiO2 template (KIT-6) followed by subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…−1 ·h −1 at 0.35 V vs. RHE without any degradation was achieved. 62 Based on the XPS and electrochemical analyses, Zhang et al revealed that the content of pyrrolic-N in the N-doped carbon materials delivered a positive effect on the 2e − ORR activity. When the cathode contains more pyrrolic-N, a better 2e − ORR selectivity is achieved in the alkaline medium.…”
Section: Selectivity During the Cathodic Reduction Processmentioning
confidence: 99%
“…−1 ·h −1 at 0.35 V vs. RHE without any degradation was achieved. 62 Based on the XPS and electrochemical analyses, Zhang et al revealed that the content of pyrrolic-N in the N-doped carbon materials delivered a positive effect on the 2e − ORR activity. When the cathode contains more pyrrolic-N, a better 2e − ORR selectivity is achieved in the alkaline medium.…”
Section: Selectivity During the Cathodic Reduction Processmentioning
confidence: 99%
“…Thence, transition-metal nanoparticles loaded on carbon-based materials have emerged as promising catalysts and have been paid more attention . Moreover, the introduction of heteroatoms, such as nitrogen-doped graphene, can distinctly alter the surface electronic structure of the active sites. Regulating the electronic structure of active sites is an effective strategy in the electrochemical O 2 reduction reaction, which can be regarded as an inherent driving force significantly enhancing the chemisorption of targeted O 2 molecules . The existence of Mott–Schottky interface in transition-metal nanoparticles loaded with nitrogen-doped graphene has been proven, encouraging spontaneous charge transfer due to difference in their Fermi level and forming a special space–charge region. Metallic nanoparticles (NPs) with a higher flat band potential lead to metal NPs becoming positively charged, which is favorable for O 2 dissociation and activation .…”
Section: Introuductionmentioning
confidence: 99%
“…It is well-known that the efficient synthesis of H 2 O 2 is the key to the degradation of pollutants. 3,4 The production of H 2 O 2 is mainly based on industrial anthraquinone processes and direct mixing reaction of H 2 and O 2 . 3−5 However, these methods have been shown to have high costs, serious pollution, and high transportation risk.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As an important chemical material, hydrogen peroxide (H 2 O 2 ) is widely used in bleaching, textile factories, chemical synthesis, medical disinfection, wastewater treatment, and semiconductor manufacturing. , Among them, in the field of wastewater treatment, on-site generation of H 2 O 2 is considered as an effective process to degrade various pollutants with high efficiency and cost effectiveness. It is well-known that the efficient synthesis of H 2 O 2 is the key to the degradation of pollutants. , The production of H 2 O 2 is mainly based on industrial anthraquinone processes and direct mixing reaction of H 2 and O 2 . However, these methods have been shown to have high costs, serious pollution, and high transportation risk . Therefore, H 2 O 2 needs to be synthesized in an environmentally friendly, economical, and safe way .…”
Section: Introductionmentioning
confidence: 99%